2007
DOI: 10.1182/blood.v110.11.3324.3324
|View full text |Cite
|
Sign up to set email alerts
|

A Budget Impact Model Comparing Resource Utilization of Four Approved Therapies for Multiple Myeloma (MM) in the US.

Abstract: Background: MM treatment has changed substantially in the past 5 years as a result of the FDA approval of single agent bortezomib (VELCADE®, Vel), the combinations of thalidomide (Thalomid®, Thal) plus dexamethasone (Dex), lenalidomide (Revlimid®, Rev) plus Dex, and most recently Vel with pegylated liposomal doxorubicin (DOXIL®, Dox). The aim of this budget impact model was to evaluate the direct resource utilization of these 4 therapies, including drug cost, medical cost and cost of management of adverse even… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…Using budget impact modeling, Fullerton et al found that the total costs associated with treatment for relapsed/refractory MM were lowest with single-agent BOR compared with THALdexamethasone, LEN-dexamethasone, and BOR-liposomal doxorubicin [28]. This appears to reflect the findings of our analyses of adjusted total health care costs.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Using budget impact modeling, Fullerton et al found that the total costs associated with treatment for relapsed/refractory MM were lowest with single-agent BOR compared with THALdexamethasone, LEN-dexamethasone, and BOR-liposomal doxorubicin [28]. This appears to reflect the findings of our analyses of adjusted total health care costs.…”
Section: Discussionsupporting
confidence: 76%
“…However, only a limited number of studies have assessed the relative costs associated with these novel therapies and their cost-effectiveness compared with other therapeutic approaches [25][26][27][28][29][30][31][32][33][34][35][36][37]. In particular, very few studies have been conducted using real-world cost data and assessing the economic burden on patients.…”
Section: Introductionmentioning
confidence: 99%
“…We used the average cost of $62 000 (2012 CPI) for the transplantation, which is similar to the currently reported cost (CPI unadjusted) of autologous transplants in the United States (15,16). Estimates of treatment costs in myeloma have been published by many groups (17)(18)(19). For our model, the cost of chemotherapy was determined from the study performed by Fullerton et al (19) in which average wholesale price (AWP) was utilized for costs.…”
Section: Cost Datamentioning
confidence: 99%
“…Estimates of treatment costs in myeloma have been published by many groups (17)(18)(19). For our model, the cost of chemotherapy was determined from the study performed by Fullerton et al (19) in which average wholesale price (AWP) was utilized for costs. The drug and medical cost for one cycle of chemotherapy was estimated to be $6687 (adjusted for 2012 CPI).…”
Section: Cost Datamentioning
confidence: 99%